2004
DOI: 10.1103/physrevstab.7.123501
|View full text |Cite
|
Sign up to set email alerts
|

Generation of angular-momentum-dominated electron beams from a photoinjector

Abstract: Various projects under study require an angular-momentum-dominated electron beam generated by a photoinjector. Some of the proposals directly use the angular-momentum-dominated beams (e.g., electron cooling of heavy ions), while others require the beam to be transformed into a flat beam (e.g., possible electron injectors for light sources and linear colliders). In this paper we report our experimental study of an angular-momentum-dominated beam produced in a photoinjector, addressing the dependencies of angula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 11 publications
0
45
0
Order By: Relevance
“…The uncorrelated emittance of the magnetized beam ε u n is measured using the slit technique from the beam image at X3 and the corresponding slit images at X5. L has been obtained with the two different methods detailed in [17]. The resulting measurements for the case σ c = 0.97 mm are summarized in Table IV: within the experimental errors we observed that the measured four-dimensional (4-D) emittance ε 4D ≡ ε x n ε y n is conserved during the roundto-flat-beam transformation.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…The uncorrelated emittance of the magnetized beam ε u n is measured using the slit technique from the beam image at X3 and the corresponding slit images at X5. L has been obtained with the two different methods detailed in [17]. The resulting measurements for the case σ c = 0.97 mm are summarized in Table IV: within the experimental errors we observed that the measured four-dimensional (4-D) emittance ε 4D ≡ ε x n ε y n is conserved during the roundto-flat-beam transformation.…”
mentioning
confidence: 54%
“…After acceleration, the beam is transformed into a flat beam using three skew quadrupoles [13]. This has been verified experimentally [14,15,16,17], and transverse emittance ratios of 40-50 were reported. Theoretical analysis of the conversion of a magnetized cylindrically-symmetric beam into a flat beam has been presented [18,19] and some of the associated limitations explored [20,21].…”
mentioning
confidence: 98%
“…The downstream beamline includes quadrupoles, steering dipole magnets, and diagnostics stations. A skew-quadrupole channel can be set up as a round-to-flat-beam transformer (RFBT) to convert an incoming angular-momentum-dominated beam into a flat beam with high transverse emittance ratio [13,14]. The beamline also incorporates a four-bend magnetic bunch compressor (BC1) which, consists of four 0.2-m rectangular dipoles (B1, B2, B3, B4) with respective bending angles of (+,-,-,+) 18 • .…”
Section: Accelerator Beamline Overviewmentioning
confidence: 99%
“…Flat beams can be produced in photoinjectors by using a roundto-flat beam transformation [36,37]. In such a scheme, a beam with large angular momentum is produced in a photoinjector [38]. Upon removal of the angular momentum by applying a torque with a set of skew quadrupole, the beam has its transverse emittance repartitioned with a tunable transverse emittances ratio [39].…”
Section: Two-dimensional Limitmentioning
confidence: 99%